A3 THE LOSS OF THE CIRCADIAN CLOCK GENE BMAL1 INCREASES TUMOUR INITIATION IN APCMIN MICE. (4th March 2021) - Nunes, M; Trombley, C; Flôres, D E; Wu, G; Curran, C; Taleb, Z; Hogenesch, J B; Karpowicz, P
Abstract: Background: Circadian rhythms are autonomously running 24h cycles in bodily processes. In animals these rhythms are driven by a molecular time keeper known as the circadian clock. The clock is a transcription-translation feedback loop composed of the transcription factors Bmal1 and Clock as well as their repressors Per and Cry. The circadian clock regulates over 40% of the genome rhythmically. Chronic circadian disruption, in the case of shift work, can lead to pathologies including cancer. Colorectal cancer is most frequently initiated through a mutation in the Wnt pathway regulator, Apc . Several studies have attempted to provide a mechanistic link between cancer and circadian clock disruption but the use of mice on mixed genetic backgrounds and poor circadian models have made this link unclear. Aims: We aim to determine if the circadian clock plays a role in intestinal tumourigenesis. Methods: We crossed the Apc min mouse strain, a common intestinal tumour model, with Bmal1 mutant mice, which lack a functioning circadian clock. After creating an isogenic strain, we examined the number of tumours in control ( Bmal1 +/+ ) and clock dead ( Bmal1 -/ - ) animals. We derived organoids, a 3D cell culture method, from Apc +/+ ; Bmal1 +/+ (healthy, clock-live), Apc +/+, Bmal1 -/ - (healthy, clock-dead), Apc min ; Bmal1 +/+ (adenoma, clock-live), Apc min ; Bmal1 -/ - (adenoma, clock-live) mouse ileum and collected every 2h from 24-48h after synchronizing their circadian clock. Collected samples were sent for RNA sequencing and assessed for circadian regulated transcripts. This experiment was followed up by in vitro organoid assays. Results: The circadian clock controls 41 genes in the intestinal epithelium, including genes like Tead4 which are known to be important in intestinal biology. There are twofold more tumours in Bmal1 -/ - mice than their Bmal1 +/+ littermates, and Bmal1 -/ - tumours upregulate Tead4 and Hippo pathway targets and downregulate Wnt pathway targets. Bmal1 -/ - adenoma organoids show increased self-renewal when compared to Bmal1 +/+ adenoma organoids. However, this increase in self-renewal is lost when organoids are treated with inhibitors of the hippo pathway. Conclusions: The circadian clock is important in maintaining the health of an organism, and disruption of the clock can lead to many health consequences including cancer. We show for the first time that the circadian clock controls the hippo signaling mediator Tead4. Additionally, we show that the loss of the clock leads to an increase in the number of tumours present in the epithelium which are characterized by an increase in hippo signaling. This research shows the important of considering time of day when studying stem cells during homeostasis and in cancer. Funding Agencies: CIHRNSERC